Ecosystem Services for Planning Post-Mining Landscapes Using the DPSIR Framework - Peer von Döhren; Dagmar Haase (Land, 2023)
Mining in general, and particularly mining for energy resources such as coal and lignite, results in massive impacts on the surrounding landscape and ecosystems. Post-mining reclamation that takes account of the disturbed ecosystem services requires a research approach that links the mining impact to ecosystem functions and ecosystem service potentials. The method used in this paper combines the Driving Forces–Pressures–State–Impact–Response (DPSIR) framework and the ES cascade approach by complementing the limitations of each approach with the strengths of the other. The DPSIR framework is extended to a causal network to account for the multiple interconnected causal chains of coal and lignite mining impacts. The presented causal network supports the identification of ES indicators for the assessment, planning, and monitoring of post-mining reclamation in coal/lignite mining landscapes. The presented approach can also inform political and administrative decisions by identifying the ecosystem elements at risk of being degraded from mining.